2006
DOI: 10.1111/j.1744-7917.2006.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of the toxic properties of forest anchomanes, Anchomanes difformis against pulse beetle Callosobruchus maculatus (Coleoptera: Bruchidae)

Abstract: Laboratory experiments were carried out to investigate the efficacy of crude stem extracts of forest anchomanes, Anchomanes difformis (P. Beauv.) a plant occurring in West African forests, against the pulse beetle Callosobruchus maculatus (Fabricius). Crude stem extracts at 3% concentration showed high contact toxicity to adult beetles within 24 h after application, while it was moderately toxic to the beetles at the lowest (1%) concentration. At the highest application rate, the plant extract provided good pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 5 publications
3
54
0
Order By: Relevance
“…The act of weakening of adults by botanical powders may make them lay fewer eggs than the normal leading to less hatchability to larvae and final metamorphosis to adults. Different botanicals effectiveness at higher dosage to various storage insect pests have been reported by several authors (Huang et al, 2000;Tripathi et al, 2000;Adedire and Lajide, 2003;Akinkurolele et al, 2006;Mbailao et al, 2006;Wang et al, 2006;Negahban et al, 2007;Oni and Ileke, 2008;Shahaf et al, 2008;Ayvaz et al, 2010;Bachrouch et al, 2010;Sivakumar et al, 2010;Adedire et al, 2011;Ileke and Oni, 2011;Mahmoudvand et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The act of weakening of adults by botanical powders may make them lay fewer eggs than the normal leading to less hatchability to larvae and final metamorphosis to adults. Different botanicals effectiveness at higher dosage to various storage insect pests have been reported by several authors (Huang et al, 2000;Tripathi et al, 2000;Adedire and Lajide, 2003;Akinkurolele et al, 2006;Mbailao et al, 2006;Wang et al, 2006;Negahban et al, 2007;Oni and Ileke, 2008;Shahaf et al, 2008;Ayvaz et al, 2010;Bachrouch et al, 2010;Sivakumar et al, 2010;Adedire et al, 2011;Ileke and Oni, 2011;Mahmoudvand et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous works (Akinkurolere et al, 2006;Mbailo et al, 2006;Akinkurolere, 2007;Echereobia et al, 2010;Panchal et al, 2011) demonstrated the efficacy of different plant oils, plant extracts and dry powders of different plant parts, as protectants against storage pests.…”
Section: Introductionmentioning
confidence: 99%
“…These losses constitute a major threat to food security and availability in Nigeria (Ofuya, 2001). Losses often range between 40 and 100% in unprotected cowpea (Akinkurolere et al, 2006;Madamba et al, 2006. Over the years, especially in Nigeria and other parts of the world, successful management of this insect pest, both on the field and in storage, has been dominated by synthetic chemical control methods such as use of pirimiphos methyl, fenitrothion, methyl bromide and phosphine fumigant (Jackai and Daoust, 1986). Due to the high prices of synthetic pesticides, farmers and traders in most Nigerian markets indiscriminately apply cheap pesticides of high mammalian toxicity, to cowpea seeds; thus, exposing unsuspecting buyers to chronic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[6]). Historically, the plant materials have been in use longer than any other group, with the possible exception of Sulphur.…”
Section: Introductionmentioning
confidence: 99%